Paleogenetic analysis and radiocarbon dating on skeletal remains from the Roman necropolis of Contrada Diana (Lipari Island, Sicily). (April 2023) - Catalano, Giulio; Modi, Alessandra; Ollà, Annunziata; Giordano, Letterio; Spigo, Umberto; Liccioli, Lucia; Barone, Serena; Caramelli, David; Lari, Martina; Sineo, Luca
Highlights: The island of Lipari was an important crossroad for Mediterranean commercial trades. We found the first ancient L3e5a haplotype outside Africa. We document the relationship between Lipari and Africa during Roman period. Abstract: Lipari, the largest of the Aeolian Islands, is located in the southern Tyrrhenian Sea. Archeological evidence suggests an early human occupation starting from the Neolithic period. The island, favored by its volcanic history, was an important crossroads of cultures and commerce exchanges during prehistory up to Greek and Roman dominations. In this study, we present multidisciplinary analysis results on four skeletal remains from the necropolis of Contrada Diana attributed to the Roman period. By using Next Generation Sequencing technology we identified the biological sex and reconstructed the complete mitochondrial genome for two individuals. We retrieved the first ancient L3e5a lineage that is today present only in North and Central Africa. In addition, a 14 C dating of 2, 030 ± 45 years BP was obtained for one individual. A previous ancient DNA study has highlighted a genetic link between Sicily and the African continent at least from the Bronze Age. Our results, documenting the existence of contacts between Lipari and Africa during Roman influence, are particularly relevant to better understand the peopling of the Aeolian Archipelago when the island was a sea route of primary importance for the trade in the Mediterranean.